What is the evidence for mass gatherings during global pandemics? A rapid summary of best-available evidence - Nunan, D.; Brassey, J. (University of Oxford, Centre for Evidence-Based Medicine, 2020)
The effect of restricting and cancelling mass gatherings and sporting events on infectiousdiseases is poorly established and requires further assessment. The best-available evidencesuggests multiple-day events with crowded communal accommodations are most associated with increased risk. Mass gatherings are not homogenous and risk should be assessed on acase-by-case basis.